Diversidade genética e virulência de amostras de Brachyspira hyodysenteriae isoladas de suínos assintomáticos e com doença clínica. - José Paulo Hiroji Sato (2017)
This thesis comprised the results of two studies. First, molecular typing and epidemiological evaluation of strains of Brachyspira hyodysenteriae isolated from swine in Brazil were performed. Multilocus Sequence Typing (MLST) analysis of seven housekeeping genes was performed in 46 Brazilian B. hyodysenteriae isolates obtained from pigs in farms during outbreaks of swine dysentery. Bacterial isolation was obtained between 2011 to 2015 in cases originated from the states of Minas Gerais, São Paulo, Mato Grosso, Rio Grande do Sul and Santa Catarina, and historical 1990s isolates from farms in the state Rio Grande do Sul. An independent MLST Brazilian MLST profile was observed compared with sequences deposited in the global Brachyspira spp database. Among the Brazilian strains, molecular relationship was observed in intra-farm profiles, among farms and among states. The second project used an in vivo challenge trial in pigs to evaluate the pathogenicity, clinical and molecular characteristics of a B. hyodysenteriae strain isolated from a pig with no clinical signs of swine dysentery, and a strain obtained from an animal with typical clinical signs of the disease. Significant differences were observed between groups, regarding onset of clinical signs, proportion ofclinically affected animals and severity of gross and microscopic lesions.